Examen especial a las cuentas de ingresos y egresos y su relación con el presupuesto de la empresa municipal terminal terrestre de la ciudad de Quevedo, año 2012 - Espinoza Criollo, Vanessa Carolina (2015)
The special examination, has become a fundamental tool in achieving business and organizational goals, both in the different public and private entities. This research work is an examination of the income and expenditure accounts and its relation to the budget of the Municipal Land Terminal City Quevedo, 2012. It was made, in order to identify any weaknesses in the control structure internal and contribute to the development and optimization of public financial resources EMTTQ. Product of the investigative work, met the objectives, by developing questionnaires that allowed us to measure the performance of the company regarding the technical standards of current budget in the study period, verifying income and expenses contain their corresponding backups and they are duly justified; Likewise, the internal control of the entity was verified considering components: control environment, risk valuation, control activity, information and communication and monitoring, study reflection that this entity has a high confidence, denoting administrative management proper, but still there are certain flaws that can be corrected by the administration to improve its management and financial information it demonstrates that it has been developed taking into account the accounting principles laid down in the manual of government accounting and processed in the tool called eSIGEF, after completion of the examination could finally determine findings and recommendations to help improve the control of resources